Women: E-Entrepreneurship and Emotional Intelligence - Chaidi , Irene; Papoutsi, Chara; Drigas, Athanasios; Skianis, Charalabos (Technium Social Sciences Journal, 2022)
Gender equality is a demand in all societies and a key goal of all countries. Among the goals of equality is the entrepreneurship of women. This article attempts to present the factors that affect the equal participation of women entrepreneurs in business and e-business and the role of lifelong learning in combating inequality. Moreover, because entrepreneurship is an environment with distinct emotional and social demands over many other organizational environments, the article highlights the important role of emotional intelligence in entrepreneurship. Finally, it presents future proposals - actions for the development of the female presence in the working digital business to reduce the gap of inequality for a better, optimistic, and promising world.